2020
DOI: 10.1097/aln.0000000000003572
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Opioid Administration

Abstract: Opioids form an important component of general anesthesia and perioperative analgesia. Discharge opioid prescriptions are identified as a contributor for persistent opioid use and diversion. In parallel, there is increased enthusiasm to advocate opioid-free strategies, which include a combination of known analgesics and adjuvants, many of which are in the form of continuous infusions. This article critically reviews perioperative opioid use, especially in view of opioid-sparing versus opioid-free strategies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
120
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 154 publications
1
120
0
Order By: Relevance
“…Preventive MgSO 4 reduced total opioid consumption up to 48 h after surgery in the current study, which is consistent with prior reports but of greater magnitude (33%) [19]. In particular, due to this opioid-sparing effect, MgSO 4 has more recently been proposed as one component in different multimodal analgesic concepts in the context of opioid-free anesthesia [20]. We showed clinical utility in combination with MgSO 4 , which opioids alone cannot, to manage intraoperative nociception and postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…Preventive MgSO 4 reduced total opioid consumption up to 48 h after surgery in the current study, which is consistent with prior reports but of greater magnitude (33%) [19]. In particular, due to this opioid-sparing effect, MgSO 4 has more recently been proposed as one component in different multimodal analgesic concepts in the context of opioid-free anesthesia [20]. We showed clinical utility in combination with MgSO 4 , which opioids alone cannot, to manage intraoperative nociception and postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…Han and colleagues reported that the intraoperative administration of a loading dose of dexmedetomidine (1 μg kg -1 ) combined with sevoflurane (compared to the use of propofol) led to significant stability in blood pressure during the operative period [ 32 ]. When compared with systemic agents, regional blockade is most effective for controlling movement-evoked pain [ 33 ]. TPVB not only causes dense somatic afferent blockades, but also completely blocks transmission within the sympathetic chain (due to the anatomy of the paravertebral space).…”
Section: Discussionmentioning
confidence: 99%
“…Among available opioid-sparing agents, loco-regional blocks perhaps have the greatest benefits, whenever appropriate. This is because they can be selectively applied to a particular area of the body with no systemic side effects and they also act superiorly on pain with activity, which is functionally more important [ 45 ]. However, they are all limited by their duration of effect.…”
Section: Discussionmentioning
confidence: 99%